Schooling for sustainable development in Europe - Rolf Jucker (Springer, 2015)
This book examines the implementation of Education for Sustainable Development (ESD) programs in schools across Europe. It describes and analyzes how individual countries and the region as a whole have established teaching and learning methods to help students develop the competencies needed to be part of a sustainable society. Featuring chapters written by experts throughout Europe, the book first provides a general overview of ESD in various contexts, including the state-of-the-art of ESD theory and conceptual development; political and social analysis; the various concepts of ESD compete.